Pengaruh Pendekatan Pembelajaran Berdiferensiasi terhadap Hasil Belajar Siswa Mata Pelajaran IPAS Kelas V di SDN 45 Mataram - Herlin Juniarti; Nurhasanah; Gozin Najah Rusyada (Mataram University, 2026)
A differentiated learning approach is a teaching strategy that accommodates students’ interests, talents, learning styles, and levels of readiness. This study aimed to determine the effect of a differentiated instruction approach on the science learning outcomes of fifth-grade students at SDN 45 Mataram. The research employed a quantitative experimental method using a Nonequivalent Control Group Design with pretest-posttest procedures. The sample consisted of 49 students, including 25 students in the experimental class and 24 students in the control class. Data were collected through tests and observations, while data analysis was conducted using the Independent Samples t-test. The findings revealed that the differentiated learning approach had a significant effect on students’ science learning outcomes. This was indicated by a significance value of 0.002 (p < 0.05) and a calculated t-value of 3.202, which was higher than the table t-value of 2.011. Therefore, H₀ was rejected and Hₐ was accepted. In addition, the mean N-Gain score of 0.5702 was categorized as moderate, indicating that differentiated instruction was sufficiently effective in improving students’ understanding and learning achievement in science subjects. Thus, the differentiated learning approach can serve as an effective alternative strategy to enhance students’ active participation and academic performance in elementary school science learning.